Extraction of Bioactive Compounds From Cannabis sativa L. Flowers and/or Leaves Using Deep Eutectic Solvents - Tiago, Francisco J.; Paiva, Alexandre; Matias, Ana A.; Duarte, Ana Rita C. (Frontiers in Nutrition, 2022)
The increasing demand for medical cannabis urges the development of new and effective methods for the extraction of phytocannabinoids. Deep eutectic Solvents (DESs) are an alternative to the use of hazardous organic solvents typically used in the industry. In this study, hydrophilic and hydrophobic DESs were developed, based on terpenes, sugars, and natural organic acids, as a green extraction media for the extraction of cannabis bioactive compounds. The factors influencing the extraction of bioactive components, such as the type of DESs and extraction time were investigated. Initial screening in hemp showed that the DES composed of Menthol: Lauric acid (2:1 M ratio) had a greater extraction efficiency of CBD and CBDA (11,07 ± 0,37 mg/g) of all the tested DESs and higher than ethanol. Besides having a higher or equivalent extraction yield as the organic solvents tested, DESs showed to be more selective extracting fewer impurities, such as chlorophyll and waxes. These results coupled with the non-toxic, biodegradable, low cost and environmentally friendly characteristics of DESs, provided strong evidence that DESs represent a better alternative to organic solvents.